Pemanfaatan Media Animasi Pembelajaran Pada Materi Indahnya Kebersamaan Dengan Berjamaah Untuk Meningkatkan Kualitas Spiritual Siswa Kelas VII SMP Pelita Al-Qur’an Wonosobo - Farahlia Nurfatihah; Rifqi Muntaqo; Nur Farida (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research has the following objectives: 1) To find out about the concept of using PAI learning animation media as material about the beauty of togetherness in congregation in an effort to improve the spiritual quality of class VII students at Pelita Al-Qur'an Middle School; 2) To find out the implementation of learning material about the beauty of togetherness in congregation through the use of animation media as an effort to improve the spiritual quality of class VII students at Pelita Al-Qur'an Middle School, Wonosobo; 3) To determine the inhibiting and supporting factors in the use of PAI animation learning media in delivering beautiful material together with the congregation of class VII students at Pelita Al-Qur'an Middle School, Wonosobo.This research uses a qualitative field approach. The data sources used came from the principal of Pelita Al-Qur'an Middle School, PAI teachers and students. Data obtained using observation, interview and documentation techniques. Data analysis was carried out using data reduction, display and drawing conclusions.The results of this research show that: 1) The concept of using animated learning media refers to the character of students which is aimed at increasing their religious level, curiosity, respect for achievement, friendly or communicative, likes to read, independent, disciplined and responsible. 2) Implementation of learning with animation media in terms of material content using a forward flow, in terms of time allocation using animation media in collaboration with other media, in terms of types of animation media used, including material videos, practice videos, material song videos and story videos. exemplary story. 3) The supporting factors for implementing this media in general are that it is more interesting so that students' motivation, understanding of the material and spiritual level can easily increase, while the obstacles are the lack of infrastructure, power outages and noisy environmental conditions because they are close to the main road.